The Subaru Telescope High Dispersion Spectrograph (HDS). Issue 1 (January 2014) - Aoki, W.
Abstract The High Dispersion Spectrograph (HDS) is the échelle spectrograph for an open‐use instrument of the Subaru Telescope. The current status of the instrument is reviewed. The new image slicers that significantly improve the efficiency of observations with very high resolving power have been installed in the past three years. Brief overview of recent science results is given on studies of early generations of stars and extra‐solar planets. An upgrade plan and future prospects of this instrument are discussed. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)